Understanding the classroom teaching work: a case study focused on reflection about the teaching of linguistic knowledge - Bandeira, Bruna (Linha D'Água, 2023)
This case study, which is situated within the socio-discursive interactionism theoretical-epistemological framework, aims to evaluate the operation of two categories of analysis seeking to understand human action: resignifications and action figures. To achieve this, the study analyzes the teaching practices of a High School Senior Portuguese teacher, with the intent of highlighting how these two categories can aid the understanding of teaching work. This experimental approach examines the resignifications attributed to the treatment of the socio-interactionism perspective of language implemented by this teacher during sessions of simple self-confrontation in which he reflected on linguistic knowledge and therefore verifies whether such resignifications can work congruently together with action figures. The results pointed towards a possible correlation between the two categories, implying how thematic subjects and linguistics modes can help us to clarify human actions and their apprehension.